Indirect speech act of refusal in the Chinese linguistic and cognitive space - Babkina, Palina S. (Journal of the Belarusian State University. Philology, 2021)
The object of the research is the indirect speech act of refusal in the Chinese linguistic and cognitive space. The objective of the research is to identify the features of the use and interpretation of indirect speech acts with the intention of refusal, as well as the reasons for referring to the indirect expression of refusal in the Chinese linguistic and cognitive space. The relevance of the research is in the fact that indirect communication in the Chinese linguistic and cultural space has not been studied before. In addition, the relevance of the topic of the research is due to the rapid growth in the development of bilateral relations between the PRC and the Republic of Belarus. The study of the phenomenon of indirect communication, as well as the national-cultural specifics of speech behaviour, in turn, contributes to the successful establishment of intercultural contacts and the prevention of communicative conflicts within the framework of intercultural communication. In close connection with extralinguistic factors, a number of the indirect refusal tactics in the Chinese linguistic and cultural space are described. Structural-grammatical and lexical-phraseological means of expressing indirect refusal in the Chinese language are differentiated. In addition, linguistic means that mitigate indirect refusal to make it more tactful are allocated. It is noted that the indirect way of expressing refusal in the Chinese linguistic and cognitive space is considered more polite, contributing to the face-saving. Furthermore, the obtained results also include the identification of the number of functions of indirect expression of refusal in the Chinese social and cultural space.